2004
DOI: 10.1002/hyp.5570
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term (18‐year) changes in sulphate concentrations in two Ontario headwater lakes and their inflows in response to decreasing deposition and climate variations

Abstract: Abstract:Sulphate concentrations in two headwater lakes and their major inflows were evaluated over an 18 year period (1980-81 to 1997-98) during which time sulphate bulk deposition declined by approximately 40%. The two lake catchments represent either end of the spectrum of acid sensitivity in the Muskoka-Haliburton region of Ontario. Between 1980 and 1998, sulphate concentrations in Harp and Plastic Lakes decreased, but the decrease was much less than expected (28% and 21% respectively) given the magnitude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 47 publications
2
32
0
Order By: Relevance
“…Elevated SO 4 2-concentrations following rewetting have been observed in similar studies, and are the result of oxidation of insoluble FeS x from the sediment during desiccation (Lucassen et al, 2005;Fernandez-Alaez and Fernadez-Alaez, 2010). The decrease in pH values follows the oxidation of SO 4 2-, which is mobilised as H 2 SO 4 during rewetting (Eimers et al, 2004). The decrease in SO 4 2-following Day 11 may have indicated the onset of sulfate reduction, although this is not consistent with the observed increase in NO 2 -+ NO 3 -at around the same time, which suggested the onset of nitrification under aerobic conditions.…”
Section: Figure 4 Mean (± Se; N = 5) P Released In Water Where Sedimementioning
confidence: 88%
“…Elevated SO 4 2-concentrations following rewetting have been observed in similar studies, and are the result of oxidation of insoluble FeS x from the sediment during desiccation (Lucassen et al, 2005;Fernandez-Alaez and Fernadez-Alaez, 2010). The decrease in pH values follows the oxidation of SO 4 2-, which is mobilised as H 2 SO 4 during rewetting (Eimers et al, 2004). The decrease in SO 4 2-following Day 11 may have indicated the onset of sulfate reduction, although this is not consistent with the observed increase in NO 2 -+ NO 3 -at around the same time, which suggested the onset of nitrification under aerobic conditions.…”
Section: Figure 4 Mean (± Se; N = 5) P Released In Water Where Sedimementioning
confidence: 88%
“…There was no significant decrease at Moose Pit Brook and at 2 sites (Plastic, Chub) in Muskoka-Haliburton in central Ontario. In central Ontario, this is likely due to the strong influence that climatic variations, and in particular summer droughts have on SO 4 export in the region (Eimers and Dillon 2002;Eimers et al, 2004). Sulphate release from Muskoka-Haliburton (MUS-HAL) catchments increases dramatically following TABLE VI Significant trends (values are in mg L −1 yr −1 ) in stream chemistry and the percentage of acid anions (SO 4 + NO 3 -N) trend balanced by base cations (Ca + Mg + K) at the 17 study catchments with more than 9 years of data (using the entire data period presented in Table I prolonged summer droughts (Eimers and Dillon, 2002), and a major drought event (peak) occurred in 1998/1999 at the end of the period considered in this study.…”
Section: Trends In Runoffmentioning
confidence: 99%
“…have demonstrated that long-term or multi-season droughtinduced SO 4 mobilization retards general recovery from acidification (Eimers et al, 2004b;Jeffries et al, 2002). Hence, a possible explanation for the strong correlation between low antecedent runoff and the anthropogenically driven ANC (poll) found in this study is that a temporary lowering of the ground water level can result in a transformation of immobile sulfides to readily mobile sulfates that can be washed out during subsequent hydrological episodes.…”
Section: Discussionmentioning
confidence: 99%